Impacts of Flipped Classroom in High School Health Education. (June 2016) - Chen, Li-Ling
As advanced technology increasingly infiltrated into classroom, the flipped classroom has come to light in secondary educational settings. The flipped classroom is a new instructional approach that intends to flip the traditional teacher-centered classroom into student centered. The purpose of this research is to investigate the impact of the flipped classroom instructional pedagogy in a ninth grade health education class.